Avaliação do Glittre ADL test como instrumento de classificação da capacidade funcional em indivíduos com doenças cardiovasculares - Aline Andrioni Fernandes (2015)
The assessment of functional capacity of individuals with cardiovascular disease (CVD) can be performed by maximal tests, submaximal, scales or questionnaires. However, such tests assess activity of lower limbs, hindering a global assessment of the patient. The Glittre ADL test may represent an objective and comprehensive way of evaluating patients with CVD, based on the model of the International Classification of Functioning, Disability and Health (ICF). The test reproduces daily activities, involving upper and lower limbs, such as sitting and rising from a chair, walk up and down stairs and carrying heavy loads. The aim of this study was to determine whether the Glittre ADL test is able to differentiate functional classes when evaluating patients with CVD. Glittre ADL test, Shuttle Walking Test (SWT), Human Activity Profile (HAP) and Duke Activity Status Index (DASI) were applied in 42 volunteers. For statistic analysis, data from the SWT, HAP and DASI were divided into tertiles. The time required to complete the Glittre ADL test was compared among tertiles of SWT, DASI and HAP by analysis of variance (ANOVA one way), post-hoc Least Significant Difference (LSD). For statistic significance was considered an alpha of 5%. SPSS version 15.0 was used. Average age was 62.21 ± 12.07 and body mass index was 26.88 ± 3.68 kg / m2. Tertiles of SWT were divided into the following groups: individuals who walked less than 303.33 meters (m), between 303.33 and 440 m and above or equal to 440 m. For HAP, individuals who scored less than 64 fit in the first tertile, between 64 and 70 in the second tertile and equal to or above 70 in the third one. For DASI, individuals who obtained less than 32, between 32 and 40 and above or equal to 40. There was a significant difference in time to accomplish the Glittre ADL test between tertiles of SWT (p=0.0001). Tertile 1 was different from the second (p=0.004) and third (p=0.0001). For DASI, there was difference between groups (p=0.008). Tertile 1 was different from 2 (p=0.02) and 3 (p=0.003). For HAP, there was difference between groups (p=0.002). The difference was found between tertile 3 and tertiles 1 (p=0.001) and 2 (p=0.018). This study demonstrated that, for this sample, Glittre ADL test is able to differentiate functional classes of individuals with CVD, especially for the most functionally affected ones.